KONTRIBUSI DAN PELUANG FINTECH LENDING SYARIAH DI INDONESIA - Sunaryono Sunaryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
Current technological developments have changed consumer behavior in transactions. In addition, it changed the development of several business sectors in the economic sector. One of these businesses is fintech. Fintech in Indonesia has increased since the start of the Covid-19 pandemic. Based on data from the Central Bureau of Statistics, the contribution of the financial services sector from 2019 to 2022 has increased. In 2019 financial services contributed 2.56% of the total gross domestic product (GDP). In 2022, the third quarter, the financial service rose to 2.68% with a total value of 82.19 billion of the total GDP. The GDP amounted in 2022 is 14.525 trillion. Financial Technology is one of the business fields that has played a role in increasing this number and from several fintech categories, researchers are trying to analyze the fintech lending category. These are the following data on the development of fintech lending issued by OJK. In 2019 there were 88 fintech lending that already had permits to operate. These fintech lending consisted of 86 conventional fintech lending and 2 sharia fintech lending. In 2022, this number increased to 95 conventional fintech lending and 7 sharia fintech lending. in 2022, the value of total assets from conventional fintech is 4.99 trillion, in otwise, the value of assets of sharia fintech lending is 120 billion. This study attempts to analyze the contribution of sharia fintech lending and its opportunities in the future. This research method used is a quantitative method using secondary data from OJK and BPS from 2019 to the third quarter of 2022. The results of this study show the percentage of assets from sharia fintech lending businesses increased by more than 300% in 2022 compared to the total assets in 2019. Conclution, The sharia fintech lending sector is still a promising business field for investors and entrepreneurs.